The Legal Framework of Kafala in Algerian Law: From Event-Based Protection to a Continuous Child Welfare Model - Belkessam, Meriem; Belkessam, Fayçal (The International tax journal, 2026)
This article critically examines the Algerian legal framework governing Kafala as the primary mechanism of alternative care for children deprived of a family environment. While Algerian law establishes relatively structured procedural safeguards at the stage of attribution, it lacks effective mechanisms for post-placement monitoring and long-term supervision. Adopting a combined doctrinal and socio-legal approach, the study analyzes the relevant provisions of the Algerian Family Code and Law No. 15-12 on Child Protection, alongside institutional practices. The analysis is further situated within the normative framework of the Convention on the Rights of the Child and the interpretative guidance of the Committee on the Rights of the Child, particularly General Comment No. 14 (2013). The article argues that the Algerian system reflects an event-centered protection paradigm, in which legal safeguards are concentrated at the moment of placement but are not sustained over time. This temporal fragmentation undermines the effective realization of the child’s best interests by limiting protection to a single legal act rather than ensuring continuous oversight.The study concludes that aligning the Algerian framework with contemporary international standards requires a shift toward a continuous protection model, based on periodic review, strengthened institutional coordination, and proactive intervention mechanisms.